Prolonged Remission in Metastatic Ano‐Rectal Malignant Melanoma With Single Agent Temozolomide - Anusha Mruthyunjaya Swamy; Deepak Sundriyal; Mayank Kapoor; Mridul Khanna; Ravi Hari Phulware; Kranthi Kumar Jandrasupalli; Ujjawal Shriwastav; Amit Sehrawat (Cancer Reports)
ABSTRACT Introduction With the use of immune checkpoint inhibitors (ICIs) and targeted therapies, the clinical outcomes of metastatic melanoma have drastically improved. The current scenario has reduced the use of chemotherapy as a first‐line treatment. We report an interesting case of a patient with stage IV ano‐rectal canal malignant melanoma with an exceptional response to single‐agent temozolomide. Case Report We diagnosed a 55‐year‐old female with stage IV anorectal melanoma, BRAF V600 mutation negative. Owing to her poor performance status (PS) and non‐affordability of immunotherapy, after informed decision‐making, she was started on single agent, temozolomide. She achieved a complete metabolic response and sustained it for 3 years and continues to do so with the first‐line single‐agent temozolomide. Conclusion In a resource‐limited setting, where access to ICIs and targeted therapies is not feasible, and in patients who fail to tolerate these therapies, oral chemotherapy continues to remain effective and is worth trying in patients with poor PS.